Socio-Anthropological Factors as Sources of Desecration of Grébouo 1 Sacred Grove, Southwestern Cote d’Ivoire - Vincent, Mouroufie Kouman Kouassi; Valdier, Koffi Maxime; Benoit, Ogni Kanga; Anderson, Bitty; Seri, Gonedele Bi (European Scientific Journal, ESJ, 2019)
This paper focuses on investigating the threats affecting GrÃ©bouo 1 forest grove (GFG) and their socio-anthropological drivers. Sociological surveys consist of semi-structured interviews and individual discussions among communitiesâ€™ elders and households in four nearest villages surrounding GFG. The taboos implied a ban on damaging or disrespecting the area. Disrespecting the area included burning, hunting, cutting, and polluting the area through defecating, urinating, or sexual activities. Natives are the community that mostly (88%) collect plant resources inside GFG compared to Ivorian and West African migrants (5 and 11% respectively). For all the respondents, GFG is a place of supply (92% of the respondents) and secondly is a holy place (5% of the respondents). The rarefaction of forest resources in GFG region poses threats to the grove since the traditional beliefs ruling its management is no longer respected. The preservation of this grove necessitates the reconciliation between traditional beliefs, economic needs, and nature conservation.